DESIGN AND NUMERICAL STUDY OF SOFT SOIL IMPROVEMENT IN THE PANTAI INDAH KAPUK AREA BY USING PREFEBRICATED VERTICAL DRAINED AND VACUUM PRELOADING METHODS AND THE EFFECT OF LATERAL INFLUENCES ON SURROUNDING BUILDINGS - Mukti Muhammad Sahid, Rezky
Reclamation work on soft soils in general will cause various geotechnical problems related to soil behavior parameters including the degree of consolidation related to consolidation time, potential compressibility, and soil shear strength. One method of soil improvement that is quite popular to use is the soil improvement method with vacuum preloading. To evaluate the condition of soil behavior parameters, geotechnical investigations were carried out at the study location, namely SPT tests, laboratori test, CPT tests and monitoring (the installation of settlement plate instrumentation, inclinometers and piezometers). Vacuum preloading is one of the methods used to improve the shear strength and compressibility of soft soils. Although the application of this method has been quite a lot, the prediction of soil behavior with the vacuum preloading method is still difficult to do properly. In this case the main problem is the settlement and velocity, pressure distribution and pore water pressure. With complete data, research can be carried out using various numerical modeling references on PVD systems, namely 2D consolidation analysis and 1D simple method analysis. The results will be compared with the results of comprehensive geotechnical instrumentation readings including the load transfer mechanism.